Transformasi Konsep Bait Suci dalam Tradisi Yahudi dan Kristen Awal: Refleksi Teologis dan Praktis bagi Gereja Kontemporer - Ferry Agustian; Adu Polinico Fanggidae (Mitra Sriwijaya: Jurnal Teologi dan Pendidikan Kristen, 2026)
This study aims to examine the transformation of the meaning and function of the Temple during the Intertestamental Period and its relevance for the contemporary church. The research employs a qualitative method through literature review, historical analysis, and theological-comparative study of biblical sources and relevant academic literature. The findings indicate that during the Intertestamental Period, the Temple functioned not only as a center of worship but also as a center of national identity, religious education, and the social and political life of the Jewish people. In early Christian tradition, the understanding of the Temple underwent a significant transformation through the teachings of Jesus Christ, who presented Himself as the true Temple, and through the teachings of the Apostle Paul, who viewed the church and believers as the spiritual Temple in which the Holy Spirit dwells. This transformation shifted the focus from a physical building to a community of faith living in Christ. The study concludes that the concept of the Temple remains theologically relevant for the contemporary church, particularly in understanding God's presence, holiness, the unity of believers, and the church's role as a center for spiritual formation.